2023
DOI: 10.1002/ece3.10233
|View full text |Cite
|
Sign up to set email alerts
|

Is personality and its association with energetics sex‐specific in yellow‐necked mice Apodemus flavicollis?

Beau N. Strijker,
Karolina Iwińska,
Bram van der Zalm
et al.

Abstract: For the last two decades, behavioral physiologists aimed to explain a plausible covariation between energetics and personality, predicted by the "pace-of-life syndrome" (POLS) hypothesis. However, the results of these attempts are mixed with no definitive answer as to which of the two most acknowledged models "performance" or "allocation" predicts covariation between consistent among-individual variation in metabolism and repeatable behavior (animal personality). The general conclusion is that the association … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 95 publications
1
0
0
Order By: Relevance
“…Figure 2b) since they already engage in a sufficiently energy-saving strategy. We found heterothermy (as mentioned above), as well as BMR and exploration to be highly repeatable in our previous studies (Boratyński et al, 2019;Strijker et al, 2023); thus, the observed behavioral variation can be considered as animal personality (defined as consistent among-individual differences in behavior across time and context: Réale et al, 2007). As the phenotypic correlation between repeatable traits indicates among-individual correlation (review in Brommer & Class, 2017), our study presents the first empirical data suggesting that heterothermy (a strategy that can improve survival but impair reproduction; Dammhahn et al, 2017;Boratyński et al, 2024) is a significant component of a broader pace-of-life syndrome (Careau et al, 2008;Réale et al, 2010).…”
Section: Modelsupporting
confidence: 81%
“…Figure 2b) since they already engage in a sufficiently energy-saving strategy. We found heterothermy (as mentioned above), as well as BMR and exploration to be highly repeatable in our previous studies (Boratyński et al, 2019;Strijker et al, 2023); thus, the observed behavioral variation can be considered as animal personality (defined as consistent among-individual differences in behavior across time and context: Réale et al, 2007). As the phenotypic correlation between repeatable traits indicates among-individual correlation (review in Brommer & Class, 2017), our study presents the first empirical data suggesting that heterothermy (a strategy that can improve survival but impair reproduction; Dammhahn et al, 2017;Boratyński et al, 2024) is a significant component of a broader pace-of-life syndrome (Careau et al, 2008;Réale et al, 2010).…”
Section: Modelsupporting
confidence: 81%